Comparing the Vulnerability of Password Security on Windows XP Profesional and Red Hat Linux 9 - Norkhushaini, Awang (2004)
Computer security is an important element that should be consider in computer networking. The basic element in computer security is password security in operating systems. This research focus on Windows XP Professional and Red Hat Linux 9 operating systems because both of these platform is popular used by Malaysian users. The main objective of this research is to identify the vulnerability of password security in both operating systems. Two computers have been connected to stimulate the attacking scenario such as in computer network. Both operating system which is Windows XP Professional and Red Hat Linux 9 have been configured with firewall that come with the system. This is to ensure that both operating systems is prevent with high level security. From the research study, found that password security on both platform is easy to be crack even firewall is configure earlier. Therefore some steps should be taken to ensure security in computer network is zero from hackers.